PENGARUH PENERAPAN E-REGISTRATION, E-FILING, DAN E-BILLING TERHADAP KEPATUHAN WAJIB PAJAK PADA (KPP) PRATAMA BULUKUMBA - Amir, Amir; Aspira, Era; Zulaeha, Sitti (Universitas Patria Artha, 2022)
This study aims to determine the effect of the appalication of the E-Registration, E-Filing, and E-Billing systems partially on taxpayer compliance at KPP Pratama Bulukumba. The variables of this study are taxpayer compliance as the dependent variable (Y), E-Registration (X1), EFiling (X2), and E-Billing (X3) as independent variable. The population of this study is individual taxpayers registered in 2021 ad many as 73,121 at KPP Pratama Bulukumba, while the sample is individual taxpayers who apply E-Registration, E-Filing, and E-Billing in fulfilling their tax obligations taken by purposive techniques. Sampling is the selection of samples with certain considerations or certain criteria and the samples used in this study were 99 respondents. Data analysis was carried out by testing data quality, classical assumption test, multiple linear regression analysis, and hypothesis. The result of this study indicate that (1) the E-Registration variable has a positive and significant taxpayer compliance, (2) the E-Filing variabel has a negative and significant effect on individual taxpayer compliance, (3) the EBilling variable has a positive effect, and significant to individual taxpayer compliance at KPP Pratama Bulukumba.